Remembering Professor Vladas Jurgutis: 120th Birthday Anniversary - Terleckas, Vladas; Jasienė, Meilė (Ekonomika, 2005)
Some features of life and activities of the prominent personality - professor Vladas Jurgutis are shown in the article. It is tried to discover him as the creator of the science of Lithuanian finances and national currency Litas, pedagogue of encyclopedic erudition, the state worker and patriot. The article is bound to commemorate 120th birthday anniversary of V. Jurgutis. V. Jurgutis was born on the 24th of October (the 5th of November) of 1885 in Palanga in the family of poor citizens. In 1897-1901 V. Jurgutis studied in the Palanga progymnasium. The further life brought him into the Samogitian Priest Seminary in Kaunas. In 1906 he graduated from the Seminary successfully. V. Jurgutis, as a very industrious student, was sent to Saint Petersburg Spiritual Academy. Here appeared his inclination to economic sciences and sociology. In 1910 V. Jurgutis graduated from Saint Petersburg Spiritual Academy and went to study at Munich University, after graduating which he was doing pastoral job in Liepaja. During the First World War he lived in Saratov. In summer 1918 he returned to Lithuania and was ordered as professor in Kaunas Priest Seminary. The events in the new independent Lithuanian state and lack of educated people involved V. Jurgutis into political life. 1920 he was elected the representative of the Seimas. V. Jurgutis in 1922 for some time worked as the Foreign Minister of the Republic of Lithuania. In 1922 life forced V. Jurgutis to take the newly created Lithuanian Bank into his hands and to worry about the strength of Lithuanian national currency Litas. The name of professor V. Jurgutis was written into history for the long year’s of pedagogy and research activities. He began his scientific research work in 1920 and the main his scientific works were: “The essence of the science of finance”, 1938; “The money”, 1938; “Banks”, 1940. While being the head of the Bank of Lithuania on the 1st of September, 1925 he began to teach in Kaunas University. When the Vilnius region was got back, at the beginning of January, 1940 V. Jurgutis began to work as the head of the Finance science chair of the Justice faculty of Vilnius University. In 1941-1943 V. Jurgutis was the head of the Economic faculty of Vilnius University. During the Hitler occupation from May 1942 till March 1943 V. Jurgutis was the chairman of the Lithuanian Science Academy. In spring 1943 V. Jurgutis together with other Lithuanian intellectuals was taken into the Stuth of concentration camp and suffered all the horrors of the camp. After getting freed he returned to suffering Lithuania. Till 1946 he was the professor of the Finance and Credit chair at Vilnius University and for some time was the head. He made many bitter remarks about the incapability in dealing with economy in the USSR and organizing of the circulation of money. Of course, such behavior of the professor could not be tolerated any longer. He was dismissed from University. In 1966 this legendary person was buried in cemetery in his native Palanga. V. Jurgutis with all his scientific activities and creations has built a monument, which, according to Horace, will not be cut by rust.